Pengaruh transparansi, akuntabilitas, dan partisipasi masyarakat terhadap pengelolaan alokasi dana desa - Ihza Pahlevi, Marhaendra; Susilowati, Endah; Widoretno, Astrini Aning (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Thel purposel of this relselarch is to telst and provel rellateld to transparelncy, accountability, and community participation relgarding thel managelmelnt of villagel fund allocations in Nganjuk District, Nganjuk Relgelncy. This typel of relselarch is using quantitativel relselarch. Relselarchelrs took thel population from villagel officials, BPD, and relprelselntativels of villagel communitiels in Nganjuk District, Nganjuk Relgelncy. Thel sampling telchniquel useld was random sampling or random sampling. Relselarch telst elquipmelnt using SPSS V26. Thel relsults showeld that transparelncy, accountability, and community participation contributeld to thel managelmelnt of villagel fund allocations in Nganjuk District, Nganjuk Relgelncy. Thus, villagel officials arel ablel to relalizel thel managelmelnt of villagel fund allocations that arel transparelnt, accountablel and participatory in accordancel with applicablel relgulations so that thely can advancel thel villagel and makel financial managelmelnt morel planneld.